ANTIOXIDANT ACTIVITY AND TOTAL PHENOL AND FLAVONOIDS ANALYSIS OF SIBERIAN GINSENG ROOT - SHETTY, NAGENDAR; HARIKA, V.; LOKRAS, SUMITRA (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study was examined to in vitro antioxidant activity and Total Phenol and Flavonoids content analysis of methanolic root extract of Eleutherococcus senticosus (Siberian ginseng). Methods: 1,1-dephenyl-2-picryl-hydrazyl free radical scavenging and FRAP assay propose that antioxidant activity of methanol root extract because of reducing capacity of the antioxidant against oxidative effects of reactive oxygen species. Results: Scavenging activity of Siberian ginseng root RC50 value was shown 713.42±11.55 µg/ml and reducing power 0.13±0.01 mmol/g was investigated. In addition, total phenol 12.6±1.13 mg GAE/g DW and total flavonoids 9.8±0.20 mg QE/g DW were recorded. Conclusion: Although all tests were performed in vitro assay, these results recommend that Siberian ginseng root may be a good source of antioxidant ingrediant.